Automatic unit test generator software by collecting run-time data - Genç, Sevdanur (Kare Publishing, 2024)
Quality and productivity needs are considered together in software. For this reason, any existing software should be tested automatically with test automation. Software test automations is automated software testing activities. Automating constantly manually written tests, on the other hand, saves time, reduces error rates, produces better quality software, and reduces costs. This study aims to produce an automatic unit testing framework that is planned to work in run-time on software products. This developed application performs unit test transformations that can respond to the desired test scenarios on the product being studied.. Java agent is used as the basis of all these transformations. All information about the objects, methods, and variables of the sample java classes to be worked on is converted into data in run-time using byte code. During this transformation, information is saved in the database, and unit tests are created automatically through the template engine. Compared to the products developed on automatic unit test generation in the literature, the opcode parsing method was developed for this study. This method reads a byte code at run-time, uses the properties of the java class it belongs to, and automatically creates the unit test class and test methods. The study can also examine different object definitions and conditional and loop structures within a method and produce alternative test scenarios. The automatic unit test scenario produced has been turned into a flexible framework that can encounter minimum errors at run-time. Considering the scarcity of studies in the field of national software testing; It is thought that the automatic unit test generation product developed within the scope of this study, using byte code, will contribute to the work area.
Keywords: Clinical Chemistry; Byte Code; Java Agent; Software Testing; The Opcode Parsing Method; Unit Test Generation; Klinik Kimya